A Foundational Jurisprudential Study on the Rulings of Birth Control in Imami Shiite Thought (Journal of the College of Basic Education, 2025)
This research presents a foundational jurisprudential study (Fiqhī Ta'ṣīlī) of the rulings on birth control within Imami thought. It addresses the Islamic perspective on population and deals with the rulings at the individual/family level and the societal level. The study analyzes the legal evidence (Quran and Sunnah), jurisprudential principles (such as the principle of permissibility - Aṣālat al-Ibāḥah), and the opinions of Imami jurists regarding various methods and their conditions (like spousal consent and absence of harm). The research also discusses and responds to common objections against birth control, emphasizing Islam's focus on quality over mere quantity. The research concludes that birth control is permissible in principle at the individual level within the legal guidelines, while regulation at the societal level is subject to the discretion of the qualified jurist (al-Faqīh al-Jāmiʿ li-l-Sharāʾiṭ) according to the public interest (al-Maṣlaḥah al-ʿĀmmah).